(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The present study was aimed to evaluate the association of serum 25-hydroxy vitamin D and parathormone in 46 patients of type 2 diabetes mellitus with diabetic retinopathy [non-proliferative, (n=27); proliferative (n=19)]. Twenty one diabetic patients without retinopathy were taken as control. Serum 25-hydroxy vitamin D and intact parathyroid hormone were measured by chemiluminescence microparticle immunoassay. Concentration of 25-hydroxy vitamin D differed significantly among groups (p=0.018) and it was significantly lower in proliferative diabetic retinopathy than no diabetic retinopathy (p=0.003). Logistic regression analysis revealed that vitamin D deficiency [25-hydroxy vitamin D <20 ng/mL] was indepen-dently associated with development of diabetic retinopathy (p=0.007, OR 20.90, 95%CI 2.33-187.23). In conclusion, vitamin D deficiency is associated with diabetic retinopathy complicating type 2 diabetes mellitus.